Exploring the Influence of NHT-Based Audio-Visual Learning on Elementary Students' Engagement in Social Studies - Darmawati, Darmawati; Nawir, Muhammad; Idawati, Idawati (Publikasi Pendidikan, 2025)
The dynamics of elementary school students' learning interests are becoming an increasingly developing discussion, but the current study interest in seeing the application of integrated learning models is increasingly complex. This study examines the effect of the Numbered Heads Together Learning Model using audio visuals on elementary school students' learning interests. The study was conducted with a quantitative design. The research method used is quantitative with a quasi-experimental design (Quasi Experiment), Pretest Posttest Control Group Design, in this design there are two classes selected randomly, then given a pretest to determine the initial conditions to determine the differences between the experimental group and the control group. Good pretest results if the experimental class scores are not significantly different. Our findings reveal that the Application of the Numbered Head Together (THT) Learning Model Using Audio Visuals on Students' Learning Interests has a significant effect. These findings provide an overview that the THT learning model with a combination of collaborative elements and interesting visual stimulation is an important aspect in elementary school students' learning interests. Future research is expected to conduct broader studies and not only be limited to certain schools.